PENGEMBANGAN E-LKPD BIOLOGI BERBASIS MODEL PEAS TERINTEGRASI LEARNING MANAGEMENT SYSTEM - Endris, Wahyu Maulana; Ginanjar, Gigin; Rayhan, Muhammad (EDUTECH : Jurnal Inovasi Pendidikan Berbantuan Teknologi, 2026)
The implementation of virtual practicums through Learning Management Systems (LMS) is often unidirectional and lacks the stimulation needed for students' critical thinking skills. Static worksheets have not been able to serve as interactive cognitive partners. This study aims to describe the development of an-Electronic Student Worksheet (E-LKPD) for Biology based on the AI-assisted PEAS (Prompt, Evaluate, Analyze, Synthesize) framework integrated within an LMS, and to evaluate its feasibility and practicality through a limited trial. This study employed a Research and Development (R&D) method using the ADDIE model, delimited to the Development phase. The limited trial subjects involved two biology subject matter experts, two media experts, and 15 Biology study program students. Data were collected using Likert scale questionnaires and analyzed using descriptive percentage statistics. Expert validation results showed an average feasibility score of 89.37% (Highly Valid), indicating scientific substantive accuracy and reliable media functionality. The practicality test by users obtained a score of 89.68% (Highly Practical), highlighting the ease of interface navigation and cognitive stimulation facilitated by the virtual assistant. In conclusion, the LMS-integrated PEAS-based Biology E-LKPD prototype is highly feasible and practical to be used as an intellectual scaffold in virtual experiments, with future prospects for effectiveness testing on a real class scale. ABSTRAK Pelaksanaan praktikum secara virtual melalui Learning Management System (LMS) sering kali berjalan satu arah dan kurang menstimulasi keterampilan berpikir kritis mahasiswa. Lembar kerja statis belum mampu menjadi mitra kognitif yang interaktif. Penelitian ini bertujuan untuk mendeskripsikan pengembangan Lembar Kerja Peserta Didik Elektronik (E-LKPD) Biologi berbasis kerangka PEAS (Prompt, Evaluate, Analyze, Synthesize) berbantuan kecerdasan buatan yang terintegrasi di dalam LMS, serta mengevaluasi kelayakan dan kepraktisannya melalui uji terbatas. Penelitian ini menggunakan metode Research and Development (R&D) dengan model ADDIE yang dibatasi hingga tahap Development. Subjek uji terbatas melibatkan dua ahli materi biologi, dua ahli media, serta 15 mahasiswa program studi Biologi. Data dikumpulkan menggunakan angket skala Likert dan dianalisis dengan statistik deskriptif persentase. Hasil validasi ahli menunjukkan rata-rata skor kelayakan sebesar 89,37% (Sangat Valid), yang mengindikasikan akurasi substansi keilmuan dan keandalan fungsionalitas media. Uji kepraktisan oleh pengguna memperoleh skor 89,68% (Sangat Praktis), menyoroti kemudahan navigasi antarmuka dan stimulasi kognitif yang difasilitasi oleh asisten virtual. Kesimpulannya, purwarupa E-LKPD Biologi berbasis PEAS yang terintegrasi LMS ini sangat layak dan praktis digunakan sebagai perancah intelektual dalam eksperimen virtual, dengan prospek lanjutan untuk diuji efektivitasnya pada skala kelas yang riil.